Functional independence in the Finnish spinal cord injury population - Majamäki, Kirsi; Tallqvist, Susanna; Vainionpää, Aki; Koskinen, Eerika; Kauppila, Anna-Maija; Bergman, Paula; Anttila, Heidi; Hämäläinen, Harri; Täckman, Anni; Kallinen, Mauri; Arokoski, Jari; Hiekkala, Sinikka (Spinal cord, 2022)
Study designA cross-sectional survey of the Finnish population with spinal cord injury (FinSCI database).ObjectivesTo describe the functional independence of the population with spinal cord injury (SCI) in Finland and to identify how generic and lesion characteristics affect their functional independence.SettingThe participants were recruited from the registers of three SCI outpatient clinics responsible for lifelong follow-up and care for people with SCI in Finland.MethodsThe data were retrieved from FinSCI (n = 1772). The response rate was 50% (n = 884). The Spinal Cord Independence Measure-Self Report (SCIM-SR) was used. The data were analyzed with univariate testing, factor analyses, and multiple linear regression models.ResultsThe median (percentiles 25; 75) SCIM-SR total score was 76.0 (58.8; 89.0), and the score was 18.0 (13.0; 20:0) for the self-care sub-scale, 33.0 (25.0; 39.0) for the respiration and sphincter management sub-scale and 29.0 (16.0; 36.8) for the mobility sub-scale. The higher the neurological level in groups AIS A, B, and C, the lower the functional ability. Group AIS D at any injury level had the highest level of functional ability. Age and the number of years since injury negatively influenced the SCIM-SR scores for every sub-scale.ConclusionBased on the International Spinal Cord Injury Core Data Set, the severity of SCI can differentiate persons with SCI according to their functional ability. The results suggest that SCI affects individuals’ health more than ageing alone does, thereby reducing the functional ability and independence of persons with SCI over time.